The Use of Fairy Tales in Developing Early Childhood Characters at Raudhatul Athfal (RA) Arafah - Lubis, Siti Nurhaliza; Wahyuni, Annisa; Oktarina, Hanifah (AMK : Abdi Masyarakat UIKA, 2024)
This research aims to find out how fairy tales are used to develop the character of early childhood and how the character of early childhood develops after using fairy tales. Location This research was carried out at RA Arafah, in the 2023/2024 academic year in the even semester. Early childhood education is the key to shaping children's personalities and preparing them for the next level of school. Therefore, children's education must start from an early age, including for the formation of children's character, because the most important thing in a child's development is the child's character. This research uses a qualitative type of research with the research subjects being school principals, teachers and students. Data collection tools used in this research are observation, interviews and documentation.The research results obtained by researchers were by using storytelling media or telling Fable to children as a learning tool to shape children's characters. This can be seen from the results of children's development after implementing the learning method through Fable in the classroom, then in implementing Fable you must also have techniques such as storytelling places, sitting positions, fairy tale language, teacher intonation, display of emotions, avoiding spontaneous words and ending Fable. This aims to be a supporting factor in developing the character of early childhood students. Then, after everything is implemented, the children begin to receive moral messages and stimulate a sense of responsibility in children, further increasing religious values, hard work, mutual help, cooperation and mutual cooperation at Ra Arafah. So that everything is applied to students using the fairy tale method as well as character building for young children. In this way, children will become more educated in the future because the use of Fable is very effective in character building and in the future can improve the morals and ethics of early childhood at RA Arafah.